2016
DOI: 10.1016/j.jmpt.2016.01.006
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Use of Chiropractic Care and Costs of Care Among Older Medicare Patients With Chronic Low Back Pain and Multiple Comorbidities

Abstract: Objective The purpose of this study was to determine whether use of chiropractic manipulative treatment (CMT) was associated with lower healthcare costs among multiply-comorbid Medicare beneficiaries with an episode of chronic low back pain (cLBP). Methods We conducted an observational, retrospective study of 2006–2012 Medicare fee-for-service reimbursements for 72,326 multiply-comorbid patients aged 66 and older with cLBP episodes and 1 of 4 treatment exposures: chiropractic manipulative treatment (CMT) alo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 50 publications
(62 reference statements)
2
28
0
Order By: Relevance
“…There are limited studies that evaluated clinically meaningful effect after chiropractic modality. According to the study of Weeks et al, on elderly patients with chronic LBP who used chiropractic therapy as the rst line of treatment during LBP attack, the overall cost of treatment and the length of each attack was reduced (35). The result of current study consistent with Christine et al that showed that the addition of chiropractic care to the usual medical care can improve the disability and pain intensity reduction in LBP, without report meaningful effect.…”
Section: Discussionsupporting
confidence: 83%
“…There are limited studies that evaluated clinically meaningful effect after chiropractic modality. According to the study of Weeks et al, on elderly patients with chronic LBP who used chiropractic therapy as the rst line of treatment during LBP attack, the overall cost of treatment and the length of each attack was reduced (35). The result of current study consistent with Christine et al that showed that the addition of chiropractic care to the usual medical care can improve the disability and pain intensity reduction in LBP, without report meaningful effect.…”
Section: Discussionsupporting
confidence: 83%
“…A study found that older patients with multiple comorbidities who used only chiropractic manipulative therapy during their chronic LBP episodes had lower overall costs of care, shorter episodes of LBP, and lower cost of care per episode day than patients in the other treatment groups, which included treatment by conventional medicine. 14 Adults with LBP are more physically and mentally unhealthy than those individuals without LBP. Murphy et al state that physical activity improves general health and halts the progression of chronic pain.…”
Section: Discussionmentioning
confidence: 99%
“…Access to chiropractic care appears to offset a patient's demand for primary care physicians' services, further reducing the number of opioid prescriptions written. 14 However, chiropractic care is often out of reach for many patients with chronic pain for monetary and accessibility reasons.…”
Section: Discussionmentioning
confidence: 99%
“…Because chiropractic has been covered by health plans for a number of years, a portion of chiropractic research has used claims data to examine the effect of going to a DC vs a conventional medical practitioner for care of musculoskeletal conditions. [25][26][27][28][29][30] These can be considered to be studies of the impact of the chiropractic profession. Nevertheless, there have been a number of efficacy studies of spinal manipulation itself.…”
Section: Researchmentioning
confidence: 99%